Strange gods a secular history of conversion - Jacoby, Susan 1945- (Pantheon Books, 2016)
From the best-selling author of The Age of American Unreason, a provocative social history of the secular forces driving conversion-for better and for worse-in the Western world, from the transformation of the Jewish Saul into Christianity's first proselytizer Paul to the twenty first-century revival of violent religious coercion by radical Islamic terrorists. In this original and riveting exploration, Susan Jacoby argues that conversion-especially in the free American "religious marketplace"--Is too often viewed only within the conventional and simplistic narrative of personal reinvention and divine grace. Instead, the author places conversions within a secular social context that has, at various times, included the force of a unified church and state, desire for upward economic mobility, and interreligious marriage-the latter as critical in the early Christian era as in the United States today, where half of Americans have switched faiths at least once in their adult lives. The sometimes tragic, sometimes inspiring story is shaped by the competing absolute truth claims of Catholicism, Protestantism, and Islam and their impact on Jews-the only monotheistic believers with an older historical stake. Moving through time, continents, and cultures-dealing with the often-ignored forced conversion of American slaves to Christianity as well as with the better-known story of the Spanish Inquisition and the persecution of both atheists and Christians in modern Islamic theocracies-the story also includes conversions to authoritarian secular ideologies, notably Stalinist Communism, that resemble traditional, unquestioning faith. Finally, the author examines true religious choice-a product of the Enlightenment pioneered by the U.S. Constitution. This history is punctuated by portraits of individual converts, including the Catholic Church father Augustine of Hippo; the German Jewish convert to Catholicism Edith Stein, murdered at Auschwitz and canonized by the church; boxing champion Muhammad Ali, who scandalized white Americans in the 1960s by becoming a Muslim, and even politicians such as George W. Bush and former British prime minister Tony Blair. In a forthright conclusion to this enthralling history, Strange Gods takes on the question of why the freedom to choose a religion-or to reject religion altogether-is a fundamental human rights issue that remains a breeding ground for violence in areas of the world that never experienced an Enlightenment.